Health related Quality of Life six years after bariatric surgery: factors influencing outcome - Caroline Almeida Soares (2020)
Introduction: Bariatric surgery is the only proven treatment to significantly improve obesity and its associated comorbidities. The success of bariatric surgery goes beyond weight lost: Quality of Life (QoL) is acquiring relevance when evaluating outcomes after bariatric surgery but few studies evaluated factors influencing QoL at long term. The main objective of this study is to identify factors that could affect QoL more than 5 years after bariatric surgery. Methods: We performed an observational study in which we apply "Moorehead-Ardelt Quality of Life Questionnaire" to 94 patients that were submitted to bariatric surgery with more than 5 years of follow up. Patients questionnaire score was compared to several variables: age, gender, main surgical procedures, primary or revisional surgery, complications, weight lost and improvement of comorbidities (diabetes, dyslipidemia, hypertension, musculoskeletal disorders and psychiatry pathology). Results: QoL was significantly influenced by weight loss outcomes (%Excess Weight Loss, %Total Weight Loss and final Body Mass Index). QoL was not significantly influenced by gender or age, type of surgery nor previously failed bariatric surgeries or complications. Improvement of hypertension was related to increased QoL, but improvement of other associated comorbidities did not had significant impact on patient's QoL at long-term. Conclusion: It appears that the main factors influencing long term QoL after bariatric surgery are related to weight loss outcomes.